2019
DOI: 10.1177/0022034519839438
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoadaptive Responses in the Periodontium Are Coordinated by Wnt

Abstract: Despite an extensive literature documenting the adaptive changes of bones and ligaments to mechanical forces, our understanding of how tissues actually mount a coordinated response to physical loading is astonishingly inadequate. Here, using finite element (FE) modeling and an in vivo murine model, we demonstrate the stress distributions within the periodontal ligament (PDL) caused by occlusal hyperloading. In direct response, a spatially restricted pattern of apoptosis is triggered in the stressed PDL, the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Actually, we initially hypothesized that implant hyper‐loading would result in microdamage, in view of our previous finding that hyper‐loading of a tooth produced ~ 2% strain in bone (Xu et al., 2019), and the fact that 2% strain is already close to the ultimate strain of 1.8% for cancellous bone with a modulus of 100 MPa (Fyhrie & Vashishth, 2000). So, we were aware that strains of this magnitude may be sufficient to damage bone and observed that the hyper‐loaded tooth had evidence of apoptotic cells in the PDL, which was followed shortly thereafter by extensive bone resorption nearby and ultimately by new bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, we initially hypothesized that implant hyper‐loading would result in microdamage, in view of our previous finding that hyper‐loading of a tooth produced ~ 2% strain in bone (Xu et al., 2019), and the fact that 2% strain is already close to the ultimate strain of 1.8% for cancellous bone with a modulus of 100 MPa (Fyhrie & Vashishth, 2000). So, we were aware that strains of this magnitude may be sufficient to damage bone and observed that the hyper‐loaded tooth had evidence of apoptotic cells in the PDL, which was followed shortly thereafter by extensive bone resorption nearby and ultimately by new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The axial compressive force (i.e., directed toward the sinus) applied to the top surface of an implant in normal and hyper‐loaded state was 1.37 N and 5 N, respectively. These forces were estimated from data on maximal biting forces at the incisal region (Ginot, Herrel, Claude, & Hautier, 2018), a dynamics model that predicted the force at the molar region (Ginot et al., 2018), plus estimates based on laboratory measurements of forces that crushed hard food pellets for rodents (Niver et al., 2011), plus estimates of load‐sharing among molars (Figure 1q and see (Xu et al., 2019)) in the physiological versus hyper‐loaded situations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two days after alizarin red injection, the mice were sacrificed and harvested. Samples were fixed in 4% paraformaldehyde overnight, dehydrated with 30% sucrose overnight, and then processed for hard tissue embedding and sectioning using Kawamoto's method 24 . Mineral apposition rates were calculated by measuring the distance between the calcein-labeled bone (green line) and the alizarin red-labeled bone (red line); this measurement was made at 8 distinct, randomly chosen sites around the maxillary first molars in 3 separate mice.…”
Section: Vital Dye Labeling and Quantification Of Mineral Apposition mentioning
confidence: 99%